Evaluasi Manajemen Kepemimpinan dalam Meningkatkan Profesionalitas Guru di SMP Pancasila Kota Bengkulu - Muhammad Shidiq; Dimas Sartika; Try Widyanto (Al-Khair Journal: Management Education, 2024)
Abstract: The purpose of this study was to evaluate the principal's leadership management in improving teacher professionalism at SMP Pancasila Kota Bengkulu. Using qualitative descriptive methods CIPP approach. The subjects in this study were the principal, vice principal of the curriculum, and teachers at SMP Pancasila. The results of the study can be concluded as follows; (1) Leadership has created a conducive school climate, provided advice and encouragement to school residents and implemented an attractive learning model that is contextual; (2) Input evaluation, that human resources still do not meet the standards, because this school lacks educators, while supporting facilities for the teaching and learning process are also still lacking. Funds sourced from foundations, BOS and third party assistance that are considered insufficient for school needs; (3) process evaluation, it can be seen that the principal's managerial program has been implemented based on management functions, namely: planning, organizing, supervising, and assessing well, but the level of implementation is still lacking both in quantity and quality and teacher motivation is also still lacking, it can be seen that curriculum development is still weak, at the time of conducting PBM there are still teachers who teach not in accordance with the existing material or theme,  So they don't understand the material yet. RPP does not match the learning theme; and (4) product evaluation, In general, leadership management has been achieved, although not optimally, so that the results of the evaluation can be suggested that it is necessary to improve the implementation of learning through leadership management evaluationKeywords: Evaluation, Leadership Management, Teacher Professionalism Abstrak: Tujuan penelitian ini adalah untuk mengevaluasi manjemen kepemimpinan kepala sekolah dalam meningkatkan profesionalitas guru di SMP Pancasila Kota Bengkulu. Menggunakan metode deskriptif kualitatif pendekatan CIPP. Subjek dalam penelitian ini adalah kepala sekolah, wakil kepala sekolah kurikulum, dan guru di SMP Pancasila. Hasil penelitian dapat disimpulkan sebagai berikut; (1) Kepemimpinan telah menciptakan iklim sekolah yang kondusif, memberikan nasehat dan dorongan kepada warga sekolah serta melaksanakan model pembelajaran yang menarik yang merupakan kontek; (2) Evaluasi input, bahwa SDM masih belum memenuhi standar, karena sekolah ini kekurangan tenaga pendidik, sedang fasilitas pendukung proses belajar mengajar juga masih kurang. Dana bersumber dari yayasan, BOS dan bantuan pihak ketiga yang dirasa belum mencukupi kebutuhan sekolah; (3) evaluasi proses, terlihat program manajerial Kepala Sekolah telah dilaksanakan berdasarkan fungsi–fungsi manajemen yakni: perencanaan, pengorganisasian, pengawasan, dan penilaian secara baik, namun tingkat implementasi masih kurang baik kuantitas maupun kualitas dan motivasi guru juga masih kurang, terlihat pada pengembangan kurikulum masih lemah, pada saat melakukan PBM masih ada guru yang mengajar belum sesuai dengan materi atau tema yang ada, sehingga belum memahami materi. RPP tidak sesuai tema pembelajaran; dan (4) evaluasi produk, Secara umum manajemen kepemimpinan sudah tercapai, meskipun belum maksimal, sehingga hasil evaluasi dapat disarankan perlu perbaikan pelaksanaan pembelajaran melalui evaluasi manajemen kepemimpinanKata Kunci : Evaluasi, Manjemen Kepemimpinan, Profesionalitas Guru